Progettazione di un allenamento di simulazione della competizione di taekwondo in base a frequenza cardiaca, lattato ematico e valutazione dello sforzo percepito - Samadi, M.; Nazem, F.; Gharaat, M. A. (Medicina dello Sport, 2014)
Aim. The previous studies reported of an outstanding amount of injuries during taekwondo competitions in which, the dominant mechanism results in the physical contact between the athletes. Therefore, a training program was designed considering physiological stress during a competition, in which the athlete would perform with a pad instead of a real opponent in order to prevent injury during preparatory competition. Methods. Twelve elite taekwondo players were selected (ages: 22±3 years, height: 178.66±6.58 cm, weight: 69.75±14.51 kg). VO2 max was measured using Bruce`s exhaustive test (46.22±4.61 mL/min/kg). Then the anaerobic power was measured using RAST field method (9.8±1.08 W/kg). Heart rate (HR) alterations were determined using RPE10 Borog Scale before the competition, at three intervals periods between any round and at the end of the third round. Blood lactate concentration (LA) was evaluated before and after the competition. To evaluate the ratio of fighting to non- fighting activity, a digital video camera was used. During the simulation, taekwondo players performed motor skills simulating a competition with the pads. Change of blood lactate, HR and RPE were measured and compared with competition conditions (the opponents). Data were compared by one-way repeated-measurement analysis of variance (ANOVA). Results. No significant differences were observed between the two conditions of competition and simulation training in HR, LA and RPE variables (P>0.05). Conclusion. Apparently the simulation training inflicts physiological stress on the elite athletes that may be replaced for preparatory competitions before a tournament to avoid possible sports injuries.